Pravda o Černobyle svidetelʹstva živych i mërtvych - Gubarev, Vladimir Stepanovič 1938-2022 (Komsomolʹskaja pravda, 2019)
A collection of eyewitness accounts and interviews with scientists, emergency workers, and others involved in containing the deadly fallout from the Chernobyl nuclear plant explosion
Keywords: Chernobyl Nuclear Accident, Chornobylʹ, Ukraine, 1986 / Personal narratives; Chernobyl Nuclear Accident, Chornobylʹ, Ukraine, 1986 / History / Sources; Nuclear accidents / Ukraine / Chornobylʹ / History / Sources; History of Russia. Soviet Union. Former Soviet Republics; Nuclear engineering. Atomic power; Reaktorunfall; Ukraine / Chornobylʹ; Tschernobyl; Erlebnisbericht; Gespräch